2018
DOI: 10.1038/s41598-018-34362-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of metformin on congenital muscular dystrophy type 1A disease progression in mice: a gender impact study

Abstract: Congenital muscular dystrophy with laminin α2 chain-deficiency (LAMA2-CMD) is a severe muscle disorder with complex underlying pathogenesis. We have previously employed profiling techniques to elucidate molecular patterns and demonstrated significant metabolic impairment in skeletal muscle from LAMA2-CMD patients and mouse models. Thus, we hypothesize that skeletal muscle metabolism may be a promising pharmacological target to improve muscle function in LAMA2-CMD. Here, we have investigated whether the multifu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 43 publications
4
17
0
Order By: Relevance
“…As previously described, we observed a decrease in dy 2J /dy 2J forelimb grip strength at six weeks of age [25,32] (Figure 2A,C). Notably, NAC treatment significantly prevented grip strength reduction in dy 2J /dy 2J mice (Figure 2A).…”
Section: Muscle Force Loss Is Prevented By Nac Treatmentsupporting
confidence: 87%
See 2 more Smart Citations
“…As previously described, we observed a decrease in dy 2J /dy 2J forelimb grip strength at six weeks of age [25,32] (Figure 2A,C). Notably, NAC treatment significantly prevented grip strength reduction in dy 2J /dy 2J mice (Figure 2A).…”
Section: Muscle Force Loss Is Prevented By Nac Treatmentsupporting
confidence: 87%
“…Several other compounds already approved for human use have been evaluated in different mouse models of LAMA2-CMD and include for example omigapil (tested in dy W /dy W and dy 2J /dy 2J mice) [56]; doxicycline (tested in dy W /dy W ) [57]; bortezomib (tested in dy 3K /dy 3K and dy 2J /dy 2J ) [22,35]; losartan and a losartan-derivative (tested in dy W /dy W and dy 2J /dy 2J ) [58][59][60]; metformin (tested in dy 2J /dy 2J ) [25], prednisolone (tested in dy/dy) [61] and clenbuterol (tested in dy/dy) [62]. It should be noted that these drugs only partially ameliorate disease (although it is incredibly difficult to compare studies that were performed in different mouse models, in different laboratories and with different outcome measures).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the majority of dystrophic features are similar between dy 2J /dy 2J males and females (dystrophic features in different muscle types) (Pasteuning-Vuhman et al, 2018), one has to take into consideration that gender-related phenotype differences (weight gain, creatine kinase levels (CK), water intake, muscle strength), exist in this mouse model (Fontes-Oliveira et al, 2018;Moreira Soares Oliveira et al, 2018;Pasteuning-Vuhman et al, 2018), which thus far has not been demonstrated for other LAMA2-CMD mutants. While these differences do not impact the overall disease presentation (they are rather subtle and a more severe phenotype cannot be attributed to any gender), they could significantly influence the outcomes of therapeutic strategies (Fontes-Oliveira et al, 2018). Hence, analysis of the treatment effects in dy 2J /dy 2J mice should take into account both genders separately.…”
Section: Phenotype Of Dy 2j /Dy 2j Micementioning
confidence: 97%
“…One week later, other dystrophic hallmarks (central nucleation, decreased muscle strength) are established and fully developed pathology can be observed at 6-8 weeks of age, including increased production of several extracellular matrix components, muscle atrophy and decreased body weights in both genders (Nevo et al, 2010;McKee et al, 2017;Fontes-Oliveira et al, 2018;Moreira Soares Oliveira et al, 2018; Tables 2, 3). Reduced muscle strength and mobility between 4-10 weeks of age has been clearly documented in several studies (Dadush et al, 2010;McKee et al, 2017;Fontes-Oliveira et al, 2018;Gawlik et al, 2018;Moreira Soares Oliveira et al, 2018;Pasteuning-Vuhman et al, 2018). The follow-up of the dy 2J /dy 2J mouse condition up to 34 weeks of age did not reveal significant muscle pathology progression compared to 6week-old mice (Pasteuning-Vuhman et al, 2018), except for the additional body weight loss between week 6-10 (Fontes- Oliveira et al, 2018).…”
Section: Phenotype Of Dy 2j /Dy 2j Micementioning
confidence: 99%